The Role of Binjai Resort Police in Preventing Crime Motorcycle Gangs in Binjai City - Maharrani, Siti; Elyani, Elyani; Na’im, Khairun; Darma, Mospa (Universitas Pahlawan Tuanku Tambusai, 2024)
Public concern about the increasing cases of motorcycle gangs in Binjai City. A motorcycle gang is a group of teenagers who like to ride motorcycles together, such as convoys or touring. In fact, motorcycle gangs are the same hobby of several people, but lately it has been increasingly unsettling the people of Binjai City. This study examines the reasons why motorcycle gangs commit crimes in the Binjai Police Resort Police area, and how the Binjai Resort Police handle motorcycle gang crimes in Binjai City. In this study, empirical juridical was used. This study aims to clarify the variables that allow motorcycle gangs to operate inside the Binjai Resort Police Police jurisdiction and commit crimes and how the Binjai Resort Police handle motorcycle gang crimes. Primary, secondary, and qualitative data analysis were all employed in this study. The results showed that several factors contributed to the crimes committed by the Motorcycle Gang in Binjai City., at first, the members of the Motorcycle Gang only sought identity and eventually committed the crime; economic factors, where motorcycle gang perpetrators get money to buy firearms and drugs. The efforts of the Binjai Resort Police to combat crimes committed by Motorcycle Gangs include criminal efforts, known as penal efforts, and non-penalty efforts, namely preventive efforts, namely conducting patrols and raids on the road, and pre-emtip efforts, namely providing socialization and counseling to the public about the dangers of crimes caused by the actions of Motorcycle Gang members.